2004
DOI: 10.1091/mbc.e03-07-0459
|View full text |Cite
|
Sign up to set email alerts
|

Rapid, Endoplasmic Reticulum-independent Diffusion of the Mitotic Golgi Haze

Abstract: Early in mitosis, the mammalian Golgi apparatus disassembles, and fluorescence microscopy reveals Golgi clusters and an extensive, nonresolvable haze that either represents scattered vesicles or a merged endoplasmic reticulum (ER)-Golgi compartment. To help decide between these alternatives, we have carried out a combined microscopic and pharmacological analysis, by using a BS-C-1 cell line stably coexpressing ER and Golgi markers. Video fluorescence microscopy showed that these two organelles were morphologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
76
2
4

Year Published

2004
2004
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(84 citation statements)
references
References 43 publications
2
76
2
4
Order By: Relevance
“…(Scale bar: 2 m.) (B) The late Golgi inheritance defect in the sec8 -599 strain was quantified as in Fig. 2. cytosol (43), and transmembrane Golgi proteins may travel in small vesicles, which diffuse through the cytosol quite rapidly (7). We favor the interpretation that ER-derived membranes fuse with Golgi-derived vesicles to form new cisternae, which recruit peripheral Golgi proteins from the cytosol (44).…”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…(Scale bar: 2 m.) (B) The late Golgi inheritance defect in the sec8 -599 strain was quantified as in Fig. 2. cytosol (43), and transmembrane Golgi proteins may travel in small vesicles, which diffuse through the cytosol quite rapidly (7). We favor the interpretation that ER-derived membranes fuse with Golgi-derived vesicles to form new cisternae, which recruit peripheral Golgi proteins from the cytosol (44).…”
Section: Discussionmentioning
confidence: 63%
“…It has been suggested that the Golgi fuses with the endoplasmic reticulum (ER) during mitosis and then reemerges as a separate organelle during cytokinesis (5). However, the preponderance of evidence now indicates that the mitotic Golgi consists mainly of small membrane fragments that are distinct from the ER (6)(7)(8). Yet Golgi reassembly during cytokinesis is inhibited by blocking ER export with a dominantnegative form of the Sar-1 GTPase (5, 9), possibly indicating a role for the ER in vertebrate Golgi inheritance.…”
Section: Yeast ͉ Organelle ͉ Mitosismentioning
confidence: 99%
“…At prometaphase, the released Golgi stacks undergo unstacking and vesiculation, resulting in the formation of mitotic Golgi clusters comprising vesicular and tubular mitotic Golgi fragments, whose fate in metaphase/anaphase is still debated. [18][19][20] At telophase, the mitotic Golgi fragments undergo a reverse series of changes leading to the reassembly of the stacks and eventually the Golgi ribbon formation in the two daughter cells. The mitotic Golgi ribbon disassembly has been considered as a stochastic mechanism for equal Golgi partitioning.…”
Section: Introductionmentioning
confidence: 99%
“…47,48 Other studies, however, did not find evidence for a merged ER and Golgi apparatus. [49][50][51][52] Furthermore, mitotic Golgi membranes are often found in close proximity to the spindle poles, suggesting an ER-independent but spindle-dependent partitioning mechanism. 16,49,53,54 Whether the spindle plays an active role in the division of the Golgi apparatus remains to be demonstrated, since it is so far not possible to uncouple the association of Golgi membranes from the spindle poles.…”
Section: Golgi Partitioning During Mitosismentioning
confidence: 99%
“…These approaches relied on the overexpression of chimeric proteins 47,51,52 in combination with temperature alterations to trap the molecules in the ER during mitosis. 48 There might be conditions under which Golgi enzymes enter the ER during mitosis for purposes of partitioning and/or regulation of other pathways.…”
Section: Golgi Partitioning During Mitosismentioning
confidence: 99%